Active circulation of varicella zoster virus among different age groups in Sudan. (14th December 2023) - Adam, Omer; Musa, Ahmed; Kamer, Amani; Benharrat, Safiya; Hübschen, Judith M.
Abstract: In Sudan, data on varicella infections are lacking and the vaccine is currently not in use. The aim of this study was to investigate previous exposure to varicella zoster virus (VZV) among children and adults from the general population and among health-care workers (HCWs) in Khartoum. Dried blood spot samples collected between 2015 and 2016 from 294 children aged 1‒15 years, 153 adult volunteers and 241 HCWs were investigated for the presence of VZV IgG antibodies using ELISA. The overall seroprevalence of VZV IgG antibodies among the investigated cohorts was 50.4%, ranging between 14.3% in children and 79.3% in HCWs. Seropositivity increased with age among children and HCWs ( P ⩽ 0.05). A relatively low seropositivity (64.7%) was observed among young adults and HCWs, suggesting that a high proportion of Sudanese adults remain susceptible. In hospital settings, this result implies a risk of nosocomial infection involving both HCWs and vulnerable patients. The results of this first VZV study in Sudan suggest active virus circulation in different age groups. Especially HCWs at the start of their career might benefit from vaccination, not only to save themselves from herpes zoster and its sequelae, but also to indirectly protect vulnerable patients.